Depressive Dysfunctional Attitudes and Post-Traumatic Stress in Victims of Terrorist Attacks. Issue 3 (4th March 2023) - Fausor, Rocío; García-Vera, María Paz; Morán, Noelia; Cobos, Beatriz; Navarro, Roberto; Sánchez-Marqueses, José Manuel; Gesteira, Clara; Liébana, Sara; Sanz, Jesús
ABSTRACT: The DSM-5ʹs new conception of post-traumatic stress disorder (PTSD) includes, as a diagnostic criterion, the presence of persistent and exaggerated negative beliefs, thoughts, or expectations about oneself, others, the world, and one's guilt. These symptoms increase the symptomatic similarity with major depressive disorder (MDD) and with the negative cognitive triad of Beck's cognitive theory of depression and allow us to assume that the dysfunctional attitudes that this theory proposes as a vulnerability factor for MDD could also refer to PTSD. This study aims to examine the relationship between depressive dysfunctional attitudes and the symptoms and diagnosis of PTSD. A sample of 378 adult victims of terrorism completed measures of depressive dysfunctional attitudes (DAS-A), DSM-IV post-traumatic stress symptoms (PCL-S), depressive symptoms (BDI-II), and DSM-IV diagnosis of emotional disorders (SCID-I). A significant relationship was found between depressive dysfunctional attitudes and PTSD symptomatology, even after controlling for the effect of depression, sex, age, education level, anxiety, and previous depressive episodes. It was also found that victims with PTSD, with or without MDD, had more depressive dysfunctional attitudes than those without emotional disorders and more achievement-perfectionism attitudes than victims with emotional disorders other than PTSD or MDD. The results suggest that depressive dysfunctional attitudes could be a vulnerability factor for PTSD. The results also suggest the need to refine Beck's cognitive theory proposals about dysfunctional attitudes common and specific to each emotional disorder and identify potential therapeutic targets of cognitive therapies for these disorders.